Music and states of consciousness: A narrative review of the broader significance of music to understanding absorption, mind wandering and creative thought - Palhares, Pedro T. (2024)
Due to music's extraordinary capacity to temporarily alter mental and physical states, the domain of musical experience offers a natural and accessible field of investigation for the study of states of consciousness. However, despite the continued emergence of music-related investigations into conscious experience, their research paradigms remain on the fringes of consciousness research, with the broader significance of their contributions often overlooked. In this narrative review, we aimed to address this gap by offering a twofold contribution. Firstly, we have highlighted and critically assessed key contributions of empirical research in music psychology and music neuroscience to our understanding of non-ordinary states of consciousness, such as absorption, mind wandering and creative thought, emphasizing the broader significance of exploring consciousness through music. Secondly, we have identified the unique aspects of music that offer special insight into consciousness and discussed how these aspects can shape future investigations. Overall, our review underscores the importance of integrating music into consciousness research and highlights avenues for future exploration in this interdisciplinary field.